Hospital Legal Responsibilities for Misuse of Patient Personal Data In Electronic Medical Records - Dian Ayu Lukitasari; Mohammad Zamroni; Andika Persada Putera (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
The purpose of this study was to analyze the patient's personal data protection law in the electronic medical record and to analyze the legal responsibility of the hospital for the misuse of patient's personal data in the electronic medical record. This research uses normative research methods and uses statutory and conceptual approaches. The issuance of Regulation of the Minister of Health Number 24 of 2022 concerning Medical Records which requires hospitals to maintain electronic medical records no later than December 31, 2022. The transition from conventional medical records to electronic medical records carries the risk of misusing patient personal data. The results of this study conclude that hospitals as personal data controllers and electronic system operators are required to implement Law Number 27 of 2022 concerning Protection of Personal Data in organizing electronic medical records except those specifically regulated by other laws and regulations and hospitals as corporations have legal responsibilities for misuse of patient personal data in electronic medical records, namely administrative liability, civil liability and criminal liability.